Human Development Index (HDI) in Lampung Province Period 2013-2018 - Ambya, Ambya (Faculty of Economics, Universitas Sriwijaya, 2020)
Human development index (HDI) is one of the benchmarks used to see the quality of human life as measured by looking at the level of human life quality of education, health and economy. This study aims to determine the effect of government spending from the education, health and capital expenditure sectors as well as income on the human development index. The data used is a secondary data in 7 districts in Lampung Province period of 2013-2018 which was obtained from the Directorate General of Fiscal Balance (DGFB Ministry of Finance) and the Central Statistics Agency (CSA) in Lampung province. The results of the analysis show that the government spending in the education sector and capital expenditure have a positive and significant effect on the human development index while the health sector spending as well as income have a negative and significant effect on the human development index.Â